The role of local radiotherapy following rituximab‐containing chemotherapy in patients with transformed indolent B‐cell lymphoma. (6th November 2020) - Nozaki, Kenji; Maruyama, Dai; Maeshima, Akiko Miyagi; Tajima, Kinuko; Itami, Jun; Shichijo, Takafumi; Yuda, Sayako; Suzuki, Tomotaka; Toyoda, Kosuke; Yamauchi, Nobuhiko; Makita, Shinichi; Fukuhara, Suguru; et al.
Abstract: Objectives: This study aimed to evaluate the outcomes of local radiotherapy (LRT) in patients with histologic transformation (HT) following rituximab‐containing chemotherapy. Methods: We retrospectively analysed 92 patients with biopsy‐confirmed HT undergoing rituximab‐containing chemotherapy at our institution between 2003 and 2015. Results: Of the 36 patients with limited‐stage disease at diagnosis of HT, 29 (78%) received LRT. The estimated 5‐year progression‐free survival (PFS) rate was significantly better in patients who underwent LRT than in those who did not (93% and 42%, respectively; P  < 0.05). Multivariate analyses employing age, sex, performance status, LRT and treatment response demonstrated that LRT was an independent prognostic factor for PFS (hazard ratio [HR]: 11.8; 95% confidence interval [CI]: 1.28‐108.1; P  < 0.05). Of the 32 patients who underwent LRT for HT lesion treatment, 31 (97%) did not show disease progression within radiation fields; among them, 27 patients (84%) survived without disease progression during the follow‐up period. One patient developed hypothyroidism due to LRT; the others had no acute or late‐onset complications of LRT. Conclusions: Our data support the recommendation of LRT for HT lesion treatment following rituximab‐containing chemotherapy in select patients with localised HT, as a rational treatment approach with potentially limited toxicity.